Biological foundations of successful bacteriophage therapy - Carola Venturini; Aleksandra Petrovic Fabijan; Alicia Fajardo Lubian; Stefanie Barbirz; Jonathan Iredell (EMBO Molecular Medicine, 2022)
Abstract Bacteriophages (phages) are selective viral predators of bacteria. Abundant and ubiquitous in nature, phages can be used to treat bacterial infections (phage therapy), including refractory infections and those resistant to antibiotics. However, despite an abundance of anecdotal evidence of efficacy, significant hurdles remain before routine implementation of phage therapy into medical practice, including a dearth of robust clinical trial data. Phage–bacterium interactions are complex and diverse, characterized by co‐evolution trajectories that are significantly influenced by the environments in which they occur (mammalian body sites, water, soil, etc.). An understanding of the molecular mechanisms underpinning these dynamics is essential for successful clinical translation. This review aims to cover key aspects of bacterium–phage interactions that affect bacterial killing by describing the most relevant published literature and detailing the current knowledge gaps most likely to influence therapeutic success.